Pulmonary Metastases- Imaging Spectrum from Different Primaries - Lekhyasree, Pabbu; Sravan Krishna Reddy A; Baru, Rama Krishna Rao; KS Vedaraju; Suneetha P (Asian Journal of Medical Radiological Research, 2022)
Background: Lung is an extremely common site for metastasis. Different imaging patterns of lung metastases help not to miss the diagnosis of metastasis, so that by giving early treatment, morbidity and mortality can be reduced. The aim & objective is to illustrate the different imaging patterns of pulmonary metastases from different primaries. Subjects and Methods: This is a retrospective descriptive study. We have taken 30 cases of pulmonary metastasis with different primary malignancies and observed the atypical radiologic features of metastases from different primaries. Results: In our institute out of 30 cases of pulmonary metastases of which 4 (14%) cases of Renal cell carcinoma, 2(7%) cases of testicular germ cell tumor, 4 (13%) cases of thyroid cancer, 2(7%) cases of osteosarcoma,4(13%) cases of GI tract adenocarcinoma, 3 (10%)cases of gynecological malignancies, 1(3%) case of femoral vein leiomyosarcoma, 4 (13%)cases of breast cancer, 1(3%) case of lymphoma, 5 (17%)cases of lung carcinoma showed different patterns of pulmonary metastases along with typical pattern, i.e., multiple soft tissue density nodules. Summary: The atypical radiologic features of metastases observed were cavitation, calcification, endobronchial metastases, ground-glass attenuation around mass (CT halo sign), and consolidation with or without ground-glass opacity. Conclusion: Multiple round variable-sized nodules and diffuse thickening of the interstitium are typical radiologic findings of pulmonary metastasis. Different patterns make it difficult the diagnosis of pulmonary metastases. So, the knowledge of different patterns of pulmonary metastases from different primaries helps in the early diagnosis of metastases.